Assessment of Information Technology Facilities in selected Hotels in Ikeja, Lagos. - Adeniji, Paulina Olufunke (African Journal of Hospitality and Tourism, 2011)
The research is about Hospitality and information Technology facilities in Hotels. It identifies the information Technology facilities in use in these hotels, to assess the competence of staff to use the facilities and to find out the purpose for which the facilities are used in hotels and also to assess the relevance of Information Technology facilities to the hotel operation and explore constraints to the effective use of these facilities. Six selected hotels were used for the study. The hundred and ten questionnaires were distributed to both guests and staff of these six hotels and one hundred and eighty questionnaires were received and analyzed statistically using frequency distribution, Statistical Packages for Social Sciences (SPSS) and the hypothesis was analyzed using T-Test. Results showed that not all the hotels had Information Technology facilities in use for their guests and staff could not use these facilities for easy service delivery. In conclusion, Information Technology facilities in hotels do not influence customer inflow but influence easy service delivery and customer satisfaction.
Keywords: Information Technology, ICT facilities, Hospitality, Customer Satisfaction, Service delivery